Early career choices for emergency medicine and later career destinations: national surveys of UK medical graduates - Lambert, Trevor W (JRSM Open, 2020)
OBJECTIVE: To report doctors’ early career preferences for emergency medicine, their eventual career destinations and factors influencing their career pathways. DESIGN: Self-administered questionnaire surveys. SETTING: United Kingdom. PARTICIPANTS: All graduates from all UK medical schools in selected graduation years between 1993 and 2015. MAIN OUTCOME MEASURES: Choices for preferred eventual specialty; eventual career destinations; certainty about choice of specialty; correspondence between early specialty choice for emergency medicine and eventually working in emergency medicine. RESULTS: Emergency medicine was chosen by 5.6% of graduates of 2015 when surveyed in 2016, and 7.1% of graduates of 2012 surveyed in 2015. These figures represent a modest increase compared with other recent cohorts, but there is no evidence of a sustained long-term trend of an increase. More men than women specified emergency medicine – in 2016 6.6% vs. 5.0%, and in 2015 7.9% vs. 6.5%. Doctors choosing emergency medicine were less certain about their choice than doctors choosing other specialties. Of graduates of 2005 who chose emergency medicine in year 1, only 18% were working in emergency medicine in year 10. Looking backwards, from destinations to early choices, 46% of 2005 graduates working in emergency medicine in 2015 had specified emergency medicine as their choice of eventual specialty in year 1. CONCLUSIONS: There was no substantial increase across the cohorts in choices for emergency medicine. Policy should address how to encourage more doctors to choose the specialty, and to create a future UK health service environment in which those who choose emergency medicine early on do not later change their minds in large numbers.